Karl Polanyi, the transition, and the social capital - Lošonc Alpar N. (Sociologija, 2004)
Taking into account the theoretical contributions to the genesis of capitalism the opus of Karl Polanyi represents the classical approach in the economic sociology and political economy. Describing the Speenhamland-narration in England Polanyi has thematised the contradiction that deeply characterized the capitalist system, namely the contradiction between the disembedded marketization and the societal self-defence. It is to be accentuated that this contradiction is immanent contra certain interpretations that arouse out during the last two decades. Polanyi’s critical work could not been integrated into the conservative attacks on the welfare arrangements and could not been explicated as the theory of organized welfare capitalism. The hypothesis that orientates this article is that Polanyi’s achievement is of crucial importance for the rereading of the transition-processes but it is to be corrected on the basis of certain interpretation of social capital. I argue that the tension of embedded ness and disembeddedness is at the center of Polanyi’s work. At the same time there is a dilemma in relation to the character of the meanings and forms of embedded ness. Due to the contribution of the literature on the social capital we can reuse it in the light of the solving of problems of the collective action. The level of embedded ness is not an expression of a neutral constellation. The social capital provides a framework for the explanation of the institutional constraints that are subject to conflict amongst the societal agents. In this way, the double movement that is depicted in the Great Transformation could be rearticulated by the conflict-centered view that ties in nicely with the concerns of those emphasizing the importance of voice, political goods and ethical limits of market.